1977
DOI: 10.1001/archneur.1977.00500150031005
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasound Scanning of the Carotid Bifurcation

Abstract: The results of Doppler scanning of 146 carotid bifurcations in 86 patients were correlated with carotid arteriography. The correlations for normal carotid arteries ranged from 63% to 98%; the correlation for occlusions of carotid arteries was 100%. The Doppler scan correlated in 70% to 85% of stenoses of the internal or external carotid arteries near their origins. The technique may be performed by a well-trained technician or physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1978
1978
1987
1987

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 9 publications
2
5
0
1
Order By: Relevance
“…7 " 19 The need for evaluation of carotid arterial disease has stimulated the development of sensitive noninvasive and relatively nontraumatic diagnostic methods 6 ' 817 " 22 to either supplement or replace carotid arteriography for the evaluation of patients with anatomically and hemodynamically significant extracranial carotid arterial disease. Various aspects of noninvasive extracranial carotid arterial disease testing have been reviewed by Weinberger 23 and support the proficiency of noninvasive methods to study carotid arterial disease as demonstrated by Jones et al 24 and Blackwell et al 25 In the present study, 3 complementary noninvasive tests were used to obtain anatomic-physiologic data for evaluation of atherosclerotic lesions in the extracranial carotid arterial system. These tests were used to screen 108 patients with familial hypercholesterolemia and CAD.…”
Section: Discussionsupporting
confidence: 58%
“…7 " 19 The need for evaluation of carotid arterial disease has stimulated the development of sensitive noninvasive and relatively nontraumatic diagnostic methods 6 ' 817 " 22 to either supplement or replace carotid arteriography for the evaluation of patients with anatomically and hemodynamically significant extracranial carotid arterial disease. Various aspects of noninvasive extracranial carotid arterial disease testing have been reviewed by Weinberger 23 and support the proficiency of noninvasive methods to study carotid arterial disease as demonstrated by Jones et al 24 and Blackwell et al 25 In the present study, 3 complementary noninvasive tests were used to obtain anatomic-physiologic data for evaluation of atherosclerotic lesions in the extracranial carotid arterial system. These tests were used to screen 108 patients with familial hypercholesterolemia and CAD.…”
Section: Discussionsupporting
confidence: 58%
“…Comparison of our data with those reported by Spencer et al 10 produced very similar results, while there is some discrepancy with results from Blackwell et al 12 We reported a positive angiogram as showing a stenosis of 50% or greater, as did Spencer, but this was not specified by Blackwell. If the latter considered a lesser stenosis as being positive, this may account for the variance.…”
Section: Discussionsupporting
confidence: 67%
“…All CWD scans were performed on supine patients with the 1050 DOPSCAN* imaging system and a 5 MHz transducer using the techniques described by Spencer et al' and Blackwell et al 2 CWD was interpreted as abnormal whenever there was no flow detectable (obstruction) or there was a doppier frequency shift greater than 6 KHz (> 50% stenosis). RTU studies were performed with an 8 MHz high-resolution Biosonics scannert with patients seated in a dental chair.…”
Section: Methodsmentioning
confidence: 99%